A CO2 photoreduction heterogeneous cobalt-based cocatalyst constructed via in situ electrostatic adsorption deposition. Issue 27 (14th March 2019) - Li, Qinghe; Lin, Feng; Liu, Feng; Wang, Xinchen
Abstract : The photocatalytic reduction of carbon dioxide to carbon monoxide could be achieved through the use of a cobalt based heterogeneous cocatalyst constructed via an in situ electrostatic adsorption deposition method. Abstract : Employing palygorskite (Pal) as a moderate alkaline regulator, herein we report the construction of a novel heterogeneous cobalt-based cocatalyst via an in situ electrostatic adsorption deposition process for its application to the photoreduction of CO2 to CO. Characterization results reveal that the negatively charged layer and relatively large specific surface area of Pal could mainly account for the high dispersity of cobalt on the surface of the fibrous support, thus endowing it with feasible CO2 adsorption and transformation.